Scintillation response of CsI(WO4) to irradiation; 3rd International Congress on Radiation Physics and Chemistry of Condensed Matter, High Current Electronics and Modification of Materials with Particle Beams and Plasma Flows - Ovcharenko N. V. Nataljya Vladimirovna; Yakovlev V. Yu. Viktor Yurjevich; Ganzha Yu. S. Yury Sergeevich; Trefilova L. N. Larisa Nikolaevna; Zelenskaya O. V. Olga Viktorovna; Rebrova T. P.; Gayduk O. V. Olga Vasiljevna; Sofronov D. S. Dmitry Semenovich (2012, 2012)
Title screen